Pengaruh Kecerdasan Emosional, Kecerdasan Intelektual, Love of Money Pada Persepsi Mahasiswa Mengenai Etika Profesi Akuntan - Kurniasari, Komang Intan; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 25 No 1 (2018)DO - 10.24843/EJA.2018.v25.i01.p29, 2018)
This study aims to determine the effect of emotional intelligence, intellectual intelligence, and love of money on the perception of students about professional ethics of accountants. The theory used in this study is the Motivation Theory. The population in this study is all non-regular students class of 2015 in Faculty of Economics and Business Udayana University. The number of samples used in this study were 114 respondents with the technique of determining the sample purposive sampling method. Data collection was done by questionnaire method. The data analysis technique used was multiple linear regression analysis. The results showed that emotional intelligence, intellectual intelligence and positive influence of love of money negatively affect the perception of students about professional ethics of accountants. Keywords: emotional intelligence, intellectual intelligence, love of money